2015
DOI: 10.1038/srep13762
|View full text |Cite
|
Sign up to set email alerts
|

Trends in (LaMnO3)n/(SrTiO3)m superlattices with varying layer thicknesses

Abstract: We investigate the thickness dependence of the structural, electronic, and magnetic properties of (LaMnO3)n/(SrTiO3)m (n, m = 2, 4, 6, 8) superlattices using density functional theory. The electronic structure turns out to be highly sensitive to the onsite Coulomb interaction. In contrast to bulk SrTiO3, strongly distorted O octahedra are observed in the SrTiO3 layers with a systematic off centering of the Ti atoms. The systems favour ferromagnetic spin ordering rather than the antiferromagnetic spin ordering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…The states of Ti are mostly above the Fermi level and thus empty. The charge transfer from Mn to Ti across the interface is evaluated by integrating the pDOS of Ti, which is only ∼ 0.03 electron per interfacial Ti (a negligible value), in consistent with previous reports [57,58]. In experimental sample growth process of oxides, oxygen vacancies (V O 's) seem to be inevitable, more or less [34,[76][77][78][79][80].…”
Section: Iiib Lmo/sto Heterostructuressupporting
confidence: 84%
See 1 more Smart Citation
“…The states of Ti are mostly above the Fermi level and thus empty. The charge transfer from Mn to Ti across the interface is evaluated by integrating the pDOS of Ti, which is only ∼ 0.03 electron per interfacial Ti (a negligible value), in consistent with previous reports [57,58]. In experimental sample growth process of oxides, oxygen vacancies (V O 's) seem to be inevitable, more or less [34,[76][77][78][79][80].…”
Section: Iiib Lmo/sto Heterostructuressupporting
confidence: 84%
“…In this work, the structural and magnetic properties of (001)-oriented vacuum/(LMO) n /(STO) 2 heterostructures will be studied using DFT calculation, in order to reveal the mechanism behind the thickness dependent magnetic transition. It should be noted although there have been many DFT studies on strained LMO, some of these calculations have not really put STO layer and vaccum into considerations [38][39][40], or those previous DFT methods would be failed to correctly describe the strain effect in LMO/STO heterostructures [57,58], as clarified in the following section. In addition, the (LMO) n /(STO) m superlattices without surface will also be calculated.…”
Section: Introductionmentioning
confidence: 99%
“…In the LaMnO 3 region, the Mn-O-Mn angles vary from 160°t o 165°. These values are higher than the bulk LaMnO 3[69] value of 155°and close to the La 2/3 Sr 1/3 MnO 3 value [70] of 165°. The electronic (charge) and magnetic (spin, orbital) degrees of freedom are coupled to the lattice, inducing [111] epitaxial strains, which in turn suppress Jahn-Teller distortions and favor breathing modes.…”
supporting
confidence: 48%
“…This behaviour is consistent with the prediction from previous studies. [37][38][39] We between the O2 molecule and the interacting surface species have considered different possible magnetic orderings at the were analyzed with the Lo¨wdin population scheme. Mn 3+ site in the 25% Ca-doped LaMnO3 structure and found that the ferromagnetic (FM) ordering is 0.3 eV more stable than…”
Section: Computational Detailsmentioning
confidence: 99%